The Alteration of L-Carnitine Transport and Pretreatment Effect under Glutamate Cytotoxicity on Motor Neuron-Like NSC-34 Lines - Gyawali, Asmita; Hyeon, Seung Jae; Ryu, Hoon; Kang, Young-Sook (MDPI, 2021)
L-Carnitine (LC) is essential for transporting fatty acids to the mitochondria for beta-oxidation. This study was performed to examine the alteration of the LC transport system in wild type (WT, NSC-34/hSOD1(WT)) and mutant type (MT, NSC-34/hSOD1(G93A)) amyotrophic lateral sclerosis (ALS) models. The uptake of [H-3]L-carnitine was dependent on time, temperature, concentration, sodium, pH, and energy in both cell lines. The Michaelis-Menten constant (K-m) value as well as maximum transport velocity (V-max) indicated that the MT cell lines showed the higher affinity and lower capacity transport system, compared to that of the WT cell lines. Additionally, LC uptake was inhibited by organic cationic compounds but unaffected by organic anions. OCTN1/slc22a4 and OCTN2/slc22a5 siRNA transfection study revealed both transporters are involved in LC transport in NSC-34 cell lines. Additionally, slc22a4 and slc22a5 was significantly decreased in mouse MT models compared with that in ALS WT littermate models in the immune-reactivity study. [H-3]L-Carnitine uptake and mRNA expression pattern showed the pretreatment of LC and acetyl L-carnitine (ALC) attenuated glutamate induced neurotoxicity in NSC-34 cell lines. These findings indicate that LC and ALC supplementation can prevent the neurotoxicity and neuro-inflammation induced by glutamate in motor neurons.